E0238 Effects of combined atorvastatin/coenzyme Q10 on myocardial fibrosis and malondialdehyde (MDA) and superoxide dismutase (SOD) in rat of heart failure. (17th November 2010) - Dongming, Zhao; Ping, Yang
Abstract : Objective: To observe the effects of Combined Atorvastatin/Coenzyme Q10 on myocardial fibrosis and MDA and SOD in Rat of heart failure, to explore the protective effect of Combined Atorvastatin/Coenzyme Q10 on the heart of the rat. Methods: Female Wister rats were subjected to the ligation of the anterior descending branch of the left coronary artery or sham operation during halothane anaesthesia. The rat heart failure models were established after 6 weeks. These rats were divided into four groups (n=6 each group): Sham operated group; model group; model group-atorvastatin, Rats in this treatment group were administrated by gastric perfusion of atorvastatin (10 mg/kg/day); model group-atorvastatin-Coenzyme Q10. Rats in this treatment group were administrated by gastric perfusion of atorvastatin (10 mg/kg/day) and Coenzyme Q10 (30 mg/kg/day). All treatment regimens were initiated 6 weeks after surgery and continued for 5 weeks. After Masson stain, myocardial fibrosis of these rats were observed by light microscope. The activity of serum SOD and the content of serum MDA were detected by biochemical methods. Results: Compared with that in model group, myocardial fibrosis level and MDA content was decreased in model group-atorvastatin (p<0.01). At the same time, the activity of SOD was increased (p<0.01). Compared with that in model group-atorvastatin, myocardial fibrosis level and MDA content was descreased in model group-atorvastatin-Coenzyme Q10 (p<0.05). At the same time, the activity of SOD was increased (p<0.05). Conclusion: Compared with atorvastatin, Combined atorvastatin/coenzyme Q10 could protect the myocardium further, and MAD and SOD maybe were involved in this process.